2003
DOI: 10.1039/b302036c
|View full text |Cite
|
Sign up to set email alerts
|

σ-Complex formation and oxidative nucleophilic aromatic substitution in 4-nitro-2,1,3-benzoxadiazoles

Abstract: The feasibility of carrying out nucleophilic displacement of hydrogen from highly electron-deficient heteroaromatics has been addressed through a detailed investigation of the interaction of a series of nitrobenzofuroxans 3a-i and two related heterocycles 5 and 6, with the 2-nitropropenide anion. Although this series corresponds to a large modulation in the electrophilic properties of the six-membered ring, all reactions first lead to the quantitative formation of the sigma-adducts C-3a-i, C-5 and C-6 arising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 64 publications
1
29
0
Order By: Relevance
“…Previous papers that have been already published in this field also reveal concurrent addition at unsubstituted positions in many heterocyclic systems . Terrier and co‐workers, for example, have demonstrated that the reaction of 3,5‐dinitropyridine 9 with the methoxide ion in methanol occurs more rapidly at the C‐4 position (σ‐adduct 10 ) than at the C‐2 position ,favoring the formation of the thermodynamically more stable isomer 11 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous papers that have been already published in this field also reveal concurrent addition at unsubstituted positions in many heterocyclic systems . Terrier and co‐workers, for example, have demonstrated that the reaction of 3,5‐dinitropyridine 9 with the methoxide ion in methanol occurs more rapidly at the C‐4 position (σ‐adduct 10 ) than at the C‐2 position ,favoring the formation of the thermodynamically more stable isomer 11 …”
Section: Resultsmentioning
confidence: 99%
“…This suggests that isomeric addition of phenoxide anions to Previous papers that have been already published in this field also reveal concurrent addition at unsubstituted positions in many heterocyclic systems. [24][25][26][27][28] Terrier and co-workers, for example, have demonstrated that the reaction of 3,5dinitropyridine 9 with the methoxide ion in methanol occurs more rapidly at the C-4 position ( -adduct 10) than at the C-2 position ,favoring the formation of the thermodynamically more stable isomer 11. 25 Kinetic measurements of the reactions of thiophenes 1 and 2 with the reference parasubstituted phenoxide anions 3ad were performed spectrophotometrically at or close to the absorption maxima of the -adducts 5-8 in aqueous solution at 20 • C under pseudo-first-order conditions in which the nucleophile concentration was kept in excess of the electrophiles.…”
Section: Kinetic Investigation and Theoretical Calculationsmentioning
confidence: 99%
“…[19,23,25,41,42] Another interesting result is the finding that nitrobenzoselenadiazole 1 b is 2 orders of magnitude more electrophilic than 1,3,5-trinitrobenzene 8 (E =-13.19), [35] the common reference aromatic electrophile in σ-complexation processes. [18][19][20][21][22][23][24]…”
Section: Electrophilicity Parameters For 4-nitrobenzochalcogenadizolementioning
confidence: 99%
“…(1) usually predicts rate constants of polar organic reactions within a factor of 10-100. [16,21,35,[44][45][46][47][48][49][50][51][52][53][54] Follet and co-workers [46] have shown that Eq. (1) predicts the rate constants for reactions of indol-3-ylmethylium ions with various phosphines and pyridines in dichloromethane solutions at 20°C within a factor of 0.33-87.2.…”
Section: Comparison Of Predictions Rate Constants With Experimental Rmentioning
confidence: 99%
See 1 more Smart Citation